Analysis of the Influence of Consumer Motivation, Perceptions and Attitudes on Purchase Decisions for Pork Rice Products in Oesapa Village (Case Study of Ma Nona Pork Rice Business) - Mbado, Margarethy Rohanie; Lerrick, Yudith F.; Pandie, Daud M. O. (International Journal of Economics (IJEC), 2023)
This research aims to determine the influence of consumer motivation, perceptions and attitudes on purchasing decisions for Ma Nona Pork Rice Products. This research uses quantitative research methods. The population in the study were all consumers of Ma Nona Pork Rice located in the Oesapa sub-district. The sample in this research was Ma Nona Pork Rice consumers, totaling 96 respondents. The sample data in this study used a questionnaire. The research analysis method uses Multiple Linear Regression Analysis, T Test, F Test, R² Test, and IBM SPSS Statistics 24. The research results show that consumer motivation, perceptions and attitudes simultaneously and partially have a positive influence on purchasing decisions for Ma Nona Pork Rice products. Based on the results of the t test in this research, it shows that the consumer motivation variable (X1) has a significant effect on the decision to purchase Ma Nona Pork Rice products, and the consumer perception variable (X2) shows a significant effect on the decision to purchase Ma Nona Pork Rice products. The consumer attitude variable (X3) shows that there is a significant influence on purchasing decisions for Ma Nona pork rice products. And the result of the coefficient of determination (R Square) is 0.285 or 28.5%, while the remaining 71.5% is influenced by other variables which are not the focus of this research. This means that after conducting research, it is known that 28.5% of Ma Nona Pork Rice Purchase Decisions are influenced by Consumer Motivation, Perception and Attitude.